Computational history and data-driven humanities : second IFIP WG 12.7 International Workshop, CHDDH 2016, Dublin, Ireland, May 25, 2016, Revised selected papers /: second IFIP WG 12.7 International Workshop, CHDDH 2016, Dublin, Ireland, May 25, 2016, Revised selected papers. (2016) - Unknown
No abstract available